2019
DOI: 10.1016/j.joms.2019.02.021
|View full text |Cite
|
Sign up to set email alerts
|

A Paradigm Shift in the Management of Cherubism? A Preliminary Report Using Imatinib

Abstract: Cherubism is an autosomal-dominant inherited mutation in the SH3BP2 gene on chromosome 4p16.3. It is characterized by bilateral symmetric fibro-osseous lesions that are limited to the maxilla and mandible. The lesions present in early childhood and typically spontaneously involute after puberty. Current standard practice is to reserve surgery for symptomatic or severely disfiguring cases. This report presents 3 patients with cherubism who exhibited marked reduction in tumor size with imatinib, a tyrosine kinas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 9 publications
0
25
0
Order By: Relevance
“…We suggest also paying more attention to a potential cherubism systemic skeletal phenotype during patient management. If this systemic skeletal cherubism phenotype is confirmed, it would simplify treatment of severe cherubism patients and allay reservations about applying a systemic treatment such as those recently published (tacrolimus [34] or imatinib [35]), to a previously believed jaw-localised disease.…”
Section: Discussionmentioning
confidence: 91%
“…We suggest also paying more attention to a potential cherubism systemic skeletal phenotype during patient management. If this systemic skeletal cherubism phenotype is confirmed, it would simplify treatment of severe cherubism patients and allay reservations about applying a systemic treatment such as those recently published (tacrolimus [34] or imatinib [35]), to a previously believed jaw-localised disease.…”
Section: Discussionmentioning
confidence: 91%
“…Alternatively intra-lesional injection of corticosteroids, systemic calcitonin, and interferon has been reported for the treatment of central giant cell granulomas of the jaw; but, they have shown variable results (31,32). More recently, oral imatinib has been used for treatment of isolated central giant cell lesions and those associated with cherubism (33); however, the data are limited to case reports and small series. The patients with NL/MGCLs in this study have shown excellent response in regression of the tumor with minimal side effects using denosumab.…”
Section: Discussionmentioning
confidence: 99%
“…This genetic disorder is related to mutations in the SH3BP2 gene encoding a tankyrase substrate. 110,111 An off-label therapeutic role of N-acetylcysteine (N-Ac) is currently being tested in diastrophic dysplasia (DTD), a severe nonlethal chondrodysplasia due to recessive mutations in the DTST gene, a cell membrane sulfate-chloride antiporter, which allows the recruitment of sulfate from the extracellular space into the cytoplasm. Preclinical studies showed promising results of N-Ac administration that acts as an intracellular sulfate source for macromolecular sulfatation in mouse models of DTD.…”
Section: Other Potentials Therapies Investigated In Animal Modelsmentioning
confidence: 99%
“…This genetic disorder is related to mutations in the SH3BP2 gene encoding a tankyrase substrate. 110,111…”
Section: X-linked Hypophosphatemiamentioning
confidence: 99%